2020
DOI: 10.3390/jpm10010019
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Hydroxyl-Methyl Butyrate, Leucine, Glutamine and Arginine Supplementation in Nutritional Management of Sarcopenia—Implications and Clinical Considerations for Type 2 Diabetes Mellitus Risk Modulation

Abstract: While onset characteristics may vary, sarcopenia gradually develops over time as a result of the aging process, leading to muscle loss, disturbance of the muscle to fat ratio, and a variety of negative symptoms undermining the wellbeing, quality of life, and lifespan in the aging population globally. There is evidence that sarcopenia may be a cause and consequence of type 2 diabetes mellitus (T2DM) in the aging population. The importance of nutritional management in the prevention and/or deceleration of sarcop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 72 publications
0
36
0
1
Order By: Relevance
“…HMB has been shown to improve strength and fatigue resistance in quadriceps muscles of humans including the elderly in multiple studies especially when HMB treatment was combined with exercise [ 53 , 95 , 103 , 126 130 ]. However, we did not observe an increase in muscle force or fatigue resistance in the EDL muscles of Ca-HMB-treated rats after unloading by HS or during reloading as compared to rats that received water.…”
Section: Discussionmentioning
confidence: 99%
“…HMB has been shown to improve strength and fatigue resistance in quadriceps muscles of humans including the elderly in multiple studies especially when HMB treatment was combined with exercise [ 53 , 95 , 103 , 126 130 ]. However, we did not observe an increase in muscle force or fatigue resistance in the EDL muscles of Ca-HMB-treated rats after unloading by HS or during reloading as compared to rats that received water.…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical indicators should be kept stable and this may occur 40 to 45 days after orthognathic surgery, as observed by other authors 19 . Although arginine and glutamine have relevant immunomodulator and anti-inflammatory effects, their ability to help lean mass recovery has not been convincingly shown among humans 8,9,[11][12][13]23,36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Various amino acids, such as β-alanine, L-glutamine, L-arginine, L-leucine and its bioactive form (hydroxymethyl butyrate) have been studied for nutritional management of sarcopenia because they are anti-catabolic and anabolic in nature [80]. For example, studies have shown that supplementation of β-alanine [81][82][83][84] may prevent and delay the progression of sarcopenia by addressing the systemic depletion of carnosine (β-alanyll-histidine), a dipeptide that acts as a pH buffer and is predominantly found in skeletal muscle.…”
Section: Supplementation With Leucine and Essential Amino Acids May Benefit Older Adults With Low Protein Intakementioning
confidence: 99%
“…For example, studies have shown that supplementation of β-alanine [81][82][83][84] may prevent and delay the progression of sarcopenia by addressing the systemic depletion of carnosine (β-alanyll-histidine), a dipeptide that acts as a pH buffer and is predominantly found in skeletal muscle. However, of these substrates, leucine is the most well studied, and requires greater understanding regarding adequate dosing and short-term versus long-term effects on muscle health [80]. Therefore, this review will discuss research surrounding the effects of leucine supplementation in older adults with low protein intake.…”
Section: Supplementation With Leucine and Essential Amino Acids May Benefit Older Adults With Low Protein Intakementioning
confidence: 99%